1994
DOI: 10.1073/pnas.91.6.2016
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric encoding/retrieval asymmetry in episodic memory: positron emission tomography findings.

Abstract: Data are reviewed from positron e on tomography studies of en ing and retrieval processes in epiodic memory. These data suggest a hpheric encodIng/retrieval asymmetry model of prefontal involvement in encoding and retrieval of episodic memory. According to this model, the left and rit prefrontal lobes are part of an extensive neuronal network that subserves episodic remember-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

118
698
15
24

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,431 publications
(855 citation statements)
references
References 28 publications
118
698
15
24
Order By: Relevance
“…The present gamma responses complement previous neuroimaging data showing the putative REMO cerebral sites at frontal and anterior cingulate areas (Lepage et al, 2000;Nyberg et al, 1996;Tulving et al, 1994). This kind of activation is also confirmed by recent studies (Rossi et al, 2001;Sandrini et al, 2004), showing that the rTMS of right DLPFC mainly impaired the retrieval of the encoded visual information.…”
Section: Hera-like Asymmetric Posterior Gamma Erssupporting
confidence: 91%
See 1 more Smart Citation
“…The present gamma responses complement previous neuroimaging data showing the putative REMO cerebral sites at frontal and anterior cingulate areas (Lepage et al, 2000;Nyberg et al, 1996;Tulving et al, 1994). This kind of activation is also confirmed by recent studies (Rossi et al, 2001;Sandrini et al, 2004), showing that the rTMS of right DLPFC mainly impaired the retrieval of the encoded visual information.…”
Section: Hera-like Asymmetric Posterior Gamma Erssupporting
confidence: 91%
“…For the latter, the rTMS of left DLPFC temporarily disabled the encoding of complex pictures (i.e., the same material used for the current study), while the rTMS of right DLPFC mainly impaired the retrieval of the encoded visual information. These results agreed with the so-called hemispherical encoding retrieval asymmetry (HERA) theory on the functional inter-hemispherical asymmetry during the long-term memorization of episodes (Lepage et al, 2000;Nyberg et al, 1996;Tulving et al, 1994). This model is now the focus of a lively discussion based on an increasing number of imaging studies that have attempted to characterize other factors affecting both the hemispheric asymmetry and the functional neuroanatomical subdivisions of frontal activation (Habib et al, 2003).…”
Section: Introductionsupporting
confidence: 80%
“…Moreover, other investigations have shown that the amount of activation in this region during semantic retrieval tasks predicts better subsequent episodic memory performance compared to orthographic tasks (e.g. [26,69]). Similarly, a left inferior frontal negativity has been implicated in the retrieval and selection of semantic attributes as well as episodic encoding in a recent ERP study [48].…”
Section: Individual Differences In Cognition and Brain Agingmentioning
confidence: 91%
“…It seems less likely that a bi-directional modulation for consolidation occurs based solely on the presence of a semantic relationship, especially because the presence of a semantic relationship does not manifest until the presentation of the second word. Instead, we find it more likely that when episodic encoding activates the retrieval of semantic information (Nyberg et al, 1996;Prince et al, 2007;Tulving et al, 1994;Tulving & Markowitsch, 1998), it does so to varying degrees, based on the semantic associativity between the two items. Upon episodic memory retrieval, the semantic network is concurrently activated, and similar to the spreading-activation theory of semantic processing (Collins & Loftus, 1975), recall of any given word facilitates the recall of a second word to a degree proportional to the semantic relatedness between the two words.…”
Section: Discussionmentioning
confidence: 64%
“…Neuroimaging evidence supports the existence of separate but highly interconnected semantic and episodic memory systems during encoding, consolidation, and retrieval (Burianova & Grady, 2007;Cabeza & Nyberg, 2000;Lepage et al, 2000;Moscovitch et al, 2005;Prince et al, 2005Prince et al, , 2007Rajah & McIntosh, 2005;Wiggs et al, 1999). It is hypothesized that episodic encoding is critically dependent upon the integrity of the semantic memory system, because all information encoded into episodic memory first passes through and activates the semantic memory system (Nyberg et al, 1996;Prince et al, 2007;Tulving et al, 1994;Tulving & Markowitsch, 1998). Episodic memory tasks instructing subjects to elaborate on the semantic features of objects during learning result in increased encoding (Craik & Tulving, 1975;Schulman, 1971), presumably by increasing semantic retrieval beyond the baseline level normally invoked in episodic tasks without such instructions.…”
Section: Introductionmentioning
confidence: 99%